1978
DOI: 10.1139/v78-464
|View full text |Cite
|
Sign up to set email alerts
|

The heat capacities and volumes of some low molecular weight amides, ketones, esters, and ethers in water over the whole solubility range

Abstract: The densities and heat capacities per unit volunle of aqueous solutions of propionan~ide, methylacetate, ethylacetate, methylethylketone and diethylketone, and bis(2-ethoxyethy1)ether were measured over the whole solubility range with a flow densirneter and a flow microcalorimeter. Most systems were studied at 10, 25, a n d 40-C. Properties of the pure liquids were also measured whenever possible. The derived apparent molal volumes 6, all decrease with concentration in the water-rich region, except with ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 6 publications
6
29
1
Order By: Relevance
“…Differences DV / (m, T) and DC p,/ (m, T) in our V / (m, T) and C p,/ (m, T) surfaces for these similar aqueous solutes can be represented by equations (6) and (7): THF arises from the addition of an oxygen atom to the ring. Our DV 2 ðDIOX-THFÞ $ 5:3 cm 3 Á mol À1 is less by 1.7 cm 3 AE mol À1 than the additive contribution of -O-to V 2 reported by Kiyohara et al [21], and is greater than that reported by Roux et al [34] by 1.2 cm 3 AE mol À1 .…”
Section: Resultscontrasting
confidence: 69%
“…Differences DV / (m, T) and DC p,/ (m, T) in our V / (m, T) and C p,/ (m, T) surfaces for these similar aqueous solutes can be represented by equations (6) and (7): THF arises from the addition of an oxygen atom to the ring. Our DV 2 ðDIOX-THFÞ $ 5:3 cm 3 Á mol À1 is less by 1.7 cm 3 AE mol À1 than the additive contribution of -O-to V 2 reported by Kiyohara et al [21], and is greater than that reported by Roux et al [34] by 1.2 cm 3 AE mol À1 .…”
Section: Resultscontrasting
confidence: 69%
“…2. OurC • p value in water at 298.15 K is found to be in a fair agreement with that reported by Desnoyers et al [10]. However, the temperature dependence of the partial molal heat capacities in our case appears to be greater.…”
Section: Resultssupporting
confidence: 93%
“…Black symbols-this work; open symbols-[10]; the lines are the linear description arises both from the large positive enthalpy of alcohol reorganization in the solute solvation shell and from the relatively weak solute-solvent interaction.Thesol H • -f (T ) curves for EtOAc in the solvents studied are fit very well with the following linear dependences: sol H • (Water) = −9.49(0.05) + 0.226(0.04) × 298.15 1 − 298.15 T s f = 0.05 kJ·mol −1 (1) sol H • (DMF) = 0.832(0.01) − 0.0005(0.0003) × (T − 298.15) s f = 0.01 kJ·mol −1 (2) sol H • (Octane) = 6.24(0.01) − 0.0155(0.003) × (T − 298.15) s f = 0.01 kJ·mol −1 (3) sol H • (OctOH) = 7.54(0.01) + 0.0105(0.0003) × (T − 298.15) s f = 0.01 kJ·mol −1…”
mentioning
confidence: 99%
“…All samples were kept in tightly sealed bottles to minimize the absorption of atmospheric moisture and CO 2 , and dried over 0.4 nm molecular sieve to reduce water content. The purity of the liquids were checked by measuring and comparing the densities at 298.15 K with their corresponding literature values [7,[9][10][11][12][13][14][15][16][17][18][19][20] in Table I. Also given in Table I are our measured or literature values of those quantities which were required in the estimation of K s,m , K E S,m , and u D .…”
Section: Methodsmentioning
confidence: 99%